Associations between serum adipocytokines and glycemic tolerance biomarkers in a rural Chinese population. - Xiaoxia Li; Yi Zhao; Yanan Jin; Tianjing Zhang; Xiaoyu Chang; Sha Liao; Hongxia Xu; Xiuying Liu; Jianjun Yang; Jianjun Zhang; Yuhong Zhang (PLoS ONE)
Although experimental studies have shown that adiponectin and leptin modulate glucose tolerance and insulin resistance, it remains unclear whether these adipocytokines exert similar effects in general human populations. We evaluated the associations of serum adiponectin and leptin with β-cell function and insulin resistance in a population with low obesity prevalence. A cross-sectional study of 783 rural residents, aged 25-74 years, recruited in Ningxia, China was conducted during 2008-2012. β-cell function and insulin resistance were estimated using the Homeostasis Model Assessment. Serum adiponectin and leptin were measured with ELISA. Serum adiponectin concentrations (mean ± SD) were highest in subjects with normal glucose tolerance (36.65 ± 61.13 μg/ml), intermediate in those with impaired fasting glucose (25.92 ± 34.48 μg/ml), and lowest in those with diabetes (15.08 ± 12.14 μg/ml) (p = 0.001). A similar pattern of differences was found for β-cell function, whereas opposite results were observed for insulin resistance and blood glucose. After adjustment for confounders including metabolic syndrome components, serum adiponectin (μg/ml) was inversely associated with β-cell function (%β) [β (95% CI): -7.57 (-12.33, -2.81)] and insulin resistance (100/%S) [β (95% CI): -0.21 (-0.33, -0.09)]. A significant inverse association also existed between serum leptin and β-cell function, but serum leptin was not significantly associated with insulin resistance. The present study suggests that adiponectin and leptin play a role in the development of insulin resistance and diabetes independent of metabolic syndrome.